Avaliação fenológica da espécie jacaranda mimosifolia d. Don na arborização urbana do município de Bagé - RS - (:unkn) unknown (Universidade Federal do Pampa, 2023)
Phenology is understood as the temporal study of the stages of the life cycle of plants, such as budding, flowering and fruiting, which occur periodically during the year. Plants are an important element of the landscape, being used in streets and squares to bring benefits to the population, such as the beautification of the landscape that can be obtained through trees with exuberant flowering. Among the species with striking flowering, there is the jacaranda-mimoso, a medium-sized tree widely used in urban afforestation. In order to understand the biological cycle of the species and make the best use of it, a phenological evaluation was carried out using the Fournier intensity methodology. The results obtained showed that, despite being considered a deciduous species, the mimosa rosewood did not present a period with total absence of leaves, which were present in the canopy throughout the year. Young leaves appeared in greater intensity in late spring and early summer, in November and December, followed by adult leaves that reached their peak of intensity in January and February. The reproductive phase of the species began in October, the month in which the first flower buds were seen, and ended in January, the last period in which flowers were seen. Unripe fruits remained present in almost all months of the year, with greater intensity in January, one month after the peak of anthesis. Ripe fruits, on the other hand, reached their peak at the height of winter, during July, the month in which the collection of seeds for seedling production is suggested. Dispersion was seen yearround, with approximately 30% Fournier intensity in all months except July and December. The results found allowed a better understanding of the phenological progression of the species, serving to improve the planning of the species in urban afforestation.
Keywords: Fenologia; Paisagismo; Jacarandá-mimoso; Phenology; Landscaping; CNPQ::CIENCIAS BIOLOGICAS